2016
DOI: 10.1111/apt.13706
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the efficacy of gut‐directed hypnotherapy is similar to that of the low FODMAP diet for the treatment of irritable bowel syndrome

Abstract: Summary Background A low fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) diet is effective in treating irritable bowel syndrome (IBS). Aim To compare the effects of gut‐directed hypnotherapy to the low FODMAP diet on gastrointestinal symptoms and psychological indices, and assess additive effects. Methods Irritable bowel syndrome patients were randomised (computer‐generated list), to receive hypnotherapy, diet or a combination. Primary end‐point: change in overall gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(163 citation statements)
references
References 31 publications
6
147
1
5
Order By: Relevance
“…These data on individual symptom response are consistent with previous findings of a non-randomised comparative trial that reported a significant difference in the numbers responding to low FODMAP dietary advice (76%) compared with standard National institute for Health and Care Excellence (NICE) guideline dietary advice (54%) 63. One recent trial also compared the low FODMAP diet with hypnotherapy in IBS 71. Both interventions improved symptoms, although there was no difference in symptom severity between groups at 6 weeks.…”
Section: The Low Fodmap Dietsupporting
confidence: 87%
See 1 more Smart Citation
“…These data on individual symptom response are consistent with previous findings of a non-randomised comparative trial that reported a significant difference in the numbers responding to low FODMAP dietary advice (76%) compared with standard National institute for Health and Care Excellence (NICE) guideline dietary advice (54%) 63. One recent trial also compared the low FODMAP diet with hypnotherapy in IBS 71. Both interventions improved symptoms, although there was no difference in symptom severity between groups at 6 weeks.…”
Section: The Low Fodmap Dietsupporting
confidence: 87%
“…The RCT previously described comparing low FODMAP advice with hypnotherapy examined the long-term symptomatic outcomes of patients 71. Lower severity scores were evident for overall symptoms in 24 patients in the low FODMAP group at 6 months compared with baseline, with an impressive 82% categorised as responders.…”
Section: The Low Fodmap Dietmentioning
confidence: 99%
“…Overall, the IBS dietary algorithm has been simplified to first-line (healthy eating, provided by any healthcare professional) and second-line (low FODMAP, provided by dietitian) dietary advice 32. An alternative to a low FODMAP diet that has shown equal efficacy is gut-directed hypnotherapy 33. In general, the low FODMAP diet remains controversial, and it still presents short-term and long-term limitations, including a high level of restriction that may be required in individual patients, the need for monitoring by an expert dietitian, potential for developing nutritional deficiencies, potential for changes in gut microbiota, lack of predictors of response as well as relative efficacy compared with other dietary, psychological or pharmacological interventions for IBS 34…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 99%
“…Table 1 reports the clinical trials that are available in the literature on the effect of a low-FODMAP diet in IBS patients [3,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. In general, most studies and one meta-analysis [6] have shown that IBS symptoms, particularly bloating and abdominal pain, may benefit from this treatment.…”
Section: Efficacy Of the Low-fodmap Diet: What Is The Quality Of Tmentioning
confidence: 99%